Dietary Advanced Glycation End Products Have Sex‐ and Age‐Dependent Effects on Vertebral Bone Microstructure and Mechanical Function in Mice. (27th November 2017) - Illien‐Jünger, Svenja; Palacio‐Mancheno, Paolo; Kindschuh, William F; Chen, Xue; Sroga, Grazyna E; Vashishth, Deepak; Iatridis, James C
ABSTRACT: Back pain is a leading cause of global disability that can arise from vertebral fracture and osteoporosis. Although poor general health and obesity are among the strongest risk factors for back pain, there is remarkably little known about how diet influences spinal diseases. Advanced glycation end‐products (AGEs) are implicated in increased fracture risk, yet no studies investigated how dietary AGEs affect spinal health. We tested the hypothesis that high dietary AGE ingestion will diminish vertebral structure and function in a sex‐ and age‐dependent manner. Female and male mice were fed low‐AGE (L‐AGE) or high‐AGE (H‐AGE) isocaloric diets for 6 and 18 months and multiple measurements of bone structure and function were taken. AGE levels in serum and cortical vertebrae were increased only for 6‐month‐old H‐AGE female mice while blood glucose and body weight remained normal for all animals. When fed an H‐AGE diet, 6‐month‐old female mice had inferior vertebral trabecular structure with decreased bone mineral density (BMD) and bone volume fraction. Biomechanical testing and analytical modeling further showed functional deterioration in 6‐month‐old H‐AGE females with reduced shear and compression moduli, and maximum load to failure. At 18 months, H‐AGE mice of both sexes had significant but small decreases in cortical BMD and thickness, yet functional biomechanical behaviors were not distinguishable from other aging changes. We conclude that an H‐AGE diet, without diabetic or overweight conditions, diminished vertebral microstructure, mechanical behaviors, and fracture resistance in young female mice in a manner suggesting accelerated bone aging. © 2017 American Society for Bone and Mineral Research.